Targeted Delivery of Erythropoietin Hybridized with Magnetic Nanocarriers for the Treatment of Central Nervous System Injury: A Literature Review - Hwang CH (Dove Medical Press, 2020)
Chang Ho Hwang Department of Physical and Rehabilitation Medicine, Chungnam National University Sejong Hospital, Chungnam National University College of Medicine, Sejong, Republic of KoreaCorrespondence: Chang Ho HwangDepartment of Physical and Rehabilitation Medicine, Chungnam National University Sejong Hospital, Chungnam National University, College of Medicine, 30099, 20, Bodeum 7-Ro, Sejong, Republic of KoreaTel + 82-44-995-4715Fax +82-44-995-2461Email chhwang1220@cnu.ac.krAbstract: Although the incidence of central nervous system injuries has continued to rise, no promising treatments have been elucidated. Erythropoietin plays an important role in neuroprotection and neuroregeneration as well as in erythropoiesis. Moreover, the current worldwide use of erythropoietin in the treatment of hematologic diseases allows for its ready application in patients with central nervous system injuries. However, erythropoietin has a very short therapeutic time window (within 6– 8 hours) after injury, and it has both hematopoietic and nonhematopoietic receptors, which exhibit heterogenic and phylogenetic differences. These differences lead to limited amounts of erythropoietin binding to in situ erythropoietin receptors. The lack of high-quality evidence for clinical use and the promising results of in vitro/in vivo models necessitate fast targeted delivery agents such as nanocarriers. Among current nanocarriers, noncovalent polymer-entrapping or polymer-adsorbing erythropoietin obtained by nanospray drying may be the most promising. With the incorporation of magnetic nanocarriers into an erythropoietin polymer, spatiotemporal external magnetic navigation is another area of great interest for targeted delivery within the therapeutic time window. Intravenous administration is the most readily used route. Manufactured erythropoietin nanocarriers should be clearly characterized using bioengineering analyses of the in vivo size distribution and the quality of entrapment or adsorption. Further preclinical trials are required to increase the therapeutic bioavailability (in vivo biological identity alteration, passage through the lung capillaries or the blood brain barrier, and timely degradation followed by removal of the nanocarriers from the body) and decrease the adverse effects (hematological complications, neurotoxicity, and cytotoxicity), especially of the nanocarrier.Keywords: erythropoietin, nanoparticles, polymers, magnetics, central nervous system, regeneration